Mosques and Muslim Social Integration: Study of External Integration of the Muslims - Sukron Kamil; Zakiya Darojat (Faculty of Adab and Humanities, Syarif Hidayatullah State Islamic University of Jakarta., 2019)
This article aims to explore the relation between mosques and external social integration of history both classic and modern times in Indonesia which has majority Muslim societies and Europe which has the minority. The method used in this study is library research. The result shows that mosques have played important roles in making efforts for external social integration of Muslims, such as the practice of the Prophet Muhammad who united Muslim Muhajirites (those who migrated from Mecca) and Anshar (indigenous Madinah) at Madinah Mosque. Another finding shows that the traces of non-Islam are existed in the Mosques. The mosque recognized domes and towers (manarah) as non-Islamic civilizations. Mosques definitely have a significant role to strengthen the external integration of Muslim either in classical history or in contemporary time.